Multi-jet hydrodynamic surface finishing and X-ray computed tomography (X-CT) inspection of laser powder bed fused Inconel 625 fuel injection/spray nozzles - Nagalingam, Arun Prasanth (2022)
Laser powder bed fused (L-PBF) components have poor surface finish quality that hinders their use in practical applications. Surface finishing the complex passages in the L-PBF components is particularly challenging. We aimed to produce a consistent surface finish on the internal passages of direct metal laser sintered (DMLS) Inconel 625 fuel nozzles—regardless of the as-built non-uniform surface—using a multi-jet hydrodynamic finishing technique. We effectively harnessed the hydrodynamic intensity and surface finished the fuel injection/spray tips comprising multiple branches. We found profile and areal surface roughness reduced up to 90 % across all branches. Also, the peak height above the core surface Spk at the nozzle inlet reduced by 40–75 %. X-ray computed tomography (X-CT) inspection post-finishing showed that roundness and circularity of the injection/spray tips improved, while most critical nozzle dimensions were within the tolerance. The results lend further credence that the proposed technique: Multi-jet hydrodynamic cavitation abrasive finishing (MJ-HCAF) can be used to surface-finish and deploy the L-PBF fuel nozzles in practical applications—ensuring safe implementation.